Analisis Nilai Tambah Agroindustri Kopi Luwak Bumdesma Raisa, Bondowoso (Studi Kasus di UMKM Pengolahan Kopi The Idjen) - Nalurita Putri Nur Fadzilah (Fakultas Teknologi Pertanian, 2025)
Civet coffee has a special taste and is different from the taste of ordinary coffee because of its fermentation that occurs in the digestion of civets. The processing of Arabica coffee fruits into civet coffee has implications for the occurrence of value-added changes produced due to a unique processing process using certain technologies. This study aims to analyze the added value of arabica civet coffee; identify the factors that influence the extent of added value for arabica civet coffee; and provide recommendations for efforts that can be made in increasing added value for the sustainability of the Arabica civet coffee agroindustry. The research was conducted on UMKM The Idjen using the Hayami method for value-added analysis and the ISM method for the analysis of key factors in formulating recommendations. The results showed that the added value of civet green beans is Rp 37,529.24 with a ratio of 68.23%, and the added value of civet ground coffee is Rp 67,235.30 with a ratio of 18.68%. The key factors that affect the added value of civet coffee in UMKM The Idjen are the management of civets, production processes, product quality, product selling prices, and raw material prices. Efforts that can be made to enhance the added value for the sustainability of the arabica civet coffee agro-industries at The Idjen SMEs based on key factors include implementing sustainable civet coffee production management.
Reupload file repository 17 Maret 2026_Ratna
Keywords: arabica civet coffee; added value; Hayami method; ISM method